THE CONTRIBUTION OF AHMAD DONISH TO THE DESCRIPTION OF THE SOCIO-POLITICAL SYSTEM IN THE BUKHARA EMIRATE (Multidisciplinary Journal of Science and Technology, 2024)
In this article, the author analyzes the contribution of Ahmad Donish in describing the socio-political system in the Bukhara Emirate in the historical work of Ahmad Donish “History of the Mangyt Dynasty”, the range of problems and current issues. Two works by Ahmad Donish are devoted mainly to problems of history and public administration.